The worth of women : wherein is clearly revealed their nobility and their superiority to men - Fonte, Moderata, 1555-1592 (Other voice in early modern Europe., 1997)
"Written in dialogue form, the work purportedly records a conversation among seven Venetian noblewomen of widely varying age and experience, whose discussions, though lossely unified around the theme of men's unjustifiable hostility to women and possible cures for it, range over almost every aspects of their lives."--Introduction, p.1